An Analysis of User Satisfaction on the Official Website of Politeknik Aceh Selatan Using the EUCS Method - Fardiansyah, Fardiansyah; Ihsan, M Arinal; Kurniadi, Sepri (PERFECT: Journal of Smart Algorithms, 2025)
This study aims to assess user satisfaction with the evaluated information system by employing a quantitative research approach, specifically through the use of a five-point Likert scale questionnaire. Respondents were asked to rate their level of agreement with 16 structured statements designed to reflect five key dimensions of user satisfaction: content, accuracy, format, ease of use, and timeliness. The Likert scale ranged from 1 (strongly disagree) to 5 (strongly agree), allowing for the collection of measurable and standardized responses. The collected data were analyzed by calculating the Actual Satisfaction Score (SKN), which represents the total cumulative score based on all respondents’ answers. This score was then compared to the Ideal Satisfaction Score (SKI), which was determined by multiplying the total number of respondents by the total number of questions and the highest possible Likert score. In this case, with 112 valid respondents, the SKN was calculated at 7,841, while the SKI reached 8,960, resulting in a Satisfaction Percentage (PK) of 87.52%. This high level of satisfaction suggests that the system effectively meets user expectations, particularly in delivering high-quality information, ensuring timely services, and providing a user-friendly interface. These findings highlight the system’s strong performance in key usability areas and underscore its potential for further development. Furthermore, the results serve as an evidence-based foundation for future enhancements, especially in fostering user-centered, accessible, and sustainable digital services.